GE_GERICHTE C/21661/2010 vom 16. Mai 2012 - GE Cour de justice (2012)
; CONSEIL EN PLACEMENT ; RESPONSABILITÉ CONTRACTUELLE ; DETTE D'ARGENT; MONNAIE ÉTRANGÈRE | CO.74. CO.84. CO.97. CO.394. CO.42. LBVM.11